Diabetes mellitus in peripheral artery disease: Beyond a risk factor - Singh, Madhu V.; Dokun, Ayotunde O. (Frontiers in Cardiovascular Medicine, 2023)
Peripheral artery disease (PAD) is one of the major cardiovascular diseases that afflicts a large population worldwide. PAD results from occlusion of the peripheral arteries of the lower extremities. Although diabetes is a major risk factor for developing PAD, coexistence of PAD and diabetes poses significantly greater risk of developing critical limb threatening ischemia (CLTI) with poor prognosis for limb amputation and high mortality. Despite the prevalence of PAD, there are no effective therapeutic interventions as the molecular mechanism of how diabetes worsens PAD is not understood. With increasing cases of diabetes worldwide, the risk of complications in PAD have greatly increased. PAD and diabetes affect a complex web of multiple cellular, biochemical and molecular pathways. Therefore, it is important to understand the molecular components that can be targeted for therapeutic purposes. In this review, we describe some major developments in enhancing the understanding of the interactions of PAD and diabetes. We also provide results from our laboratory in this context.